Faktor-Faktor yang Mempengaruhi Anggaran Pendidikan Profesi pada Kantor Jasa Penilai Publik Sudiono Awaludin dan Rekan - Azizi, Enji; Rachmadi, Agung (Jurnal Enterpreneur dan Bisnis (JEBI), 2022)
This research is a qualitative descriptive research, which is the research directed to give the symptoms, facts or events systematically and accurately about the nature of research and analyze the truth based on the data obtained. The subject of this researchis three people consisted of one leader and two employees. The object of this research is the professional education budget of Kantor Jasa Penilai Publik (KJPP) Sudiono Awaludin dan Rekan. The data collecting techniques used were observation and interview. The data collecting instrument consisted of guideline observation and guideline interview. The data analysis was done descriptively using qualitative data analysing technique. The data analysis phase includes transcript of interview result, data reduction, triangulation and draw conclusion. The result of this research showed that the budget of professional education is needed to fulfill the elementof legality, as well as increasing the credibility of service users to maintain the existence of the company. While the factors that affect the budget of professional education at Kantor Jasa Penilai Publik (KJPP) Sudiono Awaludin dan Rekan Provinsi Lampung are the rules related to the appraisal profession, cash flow and leadership style.